STUDY OF THE SPEECH DEVELOPMENT PROCESS OF CHILDREN WITH HEARING IMPAIRMENTS (Web of Teachers: Inderscience Research, 2025)
This article provides information on the history of the development of sign language in the field of philology, umga tariff, the work of scholars. The article describes the work done to teach people with hearing impairments to speak